2017
DOI: 10.1002/cam4.1012
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cell death by pyropheophorbide‐α methyl ester‐mediated photodynamic therapy in lung cancer A549 cells

Abstract: Pyropheophorbide‐α methyl ester (MPPa) was a promising photosensitizer with stable chemical structure, strong absorption, higher tissue selectivity and longer activation wavelengths. The present study investigated the effect of MPPa‐mediated photodynamic treatment on lung cancer A549 cells as well as the underlying mechanisms. Cell Counting Kit‐8 was employed for cell viability assessment. Reactive oxygen species levels were determined by fluorescence microscopy and flow cytometry. Cell morphology was evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…MPPa was used as the photosensitizer for a better safety in humans. 11,12 The present data manifested that PDT can efficiently deactivate chemoresistant cells. A higher percentage of dead cells in A549/DDP indicated that resistant cells were more sensitive to PDT but this effect was not detected in SKOV3/DDP cells, indicating the response to PDT varied between cell types (i.e., the therapeutic regimen should be specifically set for a specific cancer type).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…MPPa was used as the photosensitizer for a better safety in humans. 11,12 The present data manifested that PDT can efficiently deactivate chemoresistant cells. A higher percentage of dead cells in A549/DDP indicated that resistant cells were more sensitive to PDT but this effect was not detected in SKOV3/DDP cells, indicating the response to PDT varied between cell types (i.e., the therapeutic regimen should be specifically set for a specific cancer type).…”
Section: Discussionsupporting
confidence: 56%
“…Intracellular ROS was detected with the DCFH-DA assay (2',7'-dichlorodihydrofluorescein diacetate; Keygen Biotech.). 12 Serum-free medium containing 10 mM DCFH-DA was added, and cells were kept in dark at 37 C for 30 min. Cells were washed with PBS, and then received flow cytometry; the fluorescence intensity reflected the level of ROS.…”
Section: Measurement Of Intracellular Rosmentioning
confidence: 99%
“…MPPa belongs to the second generation of photosensitizers and is a chlorophyll derivative (30). To date, MPPa-PdT has been used clinically for the treatment of a variety of tumors such as osteosarcoma, lung and cervical cancer (17,19,31). The present study aimed to explore the functional mechanism of MPPa-PdT in osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…These photosensitizers are slowly metabolized by the body, which leads to long periods during which light must be avoided after treatment; additionally, their composition is complex, the targeting is weak and their skin phototoxicity is strong (14)(15)(16). Pyropheophorbide-α methyl ester (MPPa) belongs to the second generation of photosensitizers; this novel type of photosensitizer exhibits strong photosensitivity, a clear chemical structure, a single component and a stable nature, and it is metabolized rapidly by the body (17)(18)(19). MPPa-PdT has been studied in multiple types of cancer such as breast, lung and prostate cancer (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation